2014
DOI: 10.1227/neu.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

Polyetheretherketone Implants for the Repair of Large Cranial Defects

Abstract: Custom-designed PEEK implants are a good option for patients with large cranial defects. The rate of complications is comparable to other implants or autologous bone. Given the large size of these defects, the aesthetic results are good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 20 publications
3
62
0
Order By: Relevance
“…A recent international, multiinstitutional report of 66 PEEK prostheses demonstrated an infection rate of 7.6%. 21 The postcranioplasty infection rate among 151 PEEK implants in our series was 6%, and, as in other studies, suggests that synthetic prostheses have infection rates similar to those with ABFs. 4,14,19,23,25,[27][28][29] Most important in our results is the favorable comparison between protocols A and B as regards the reimplantation of +ABFs despite intraoperative bone cultures of skin flora.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent international, multiinstitutional report of 66 PEEK prostheses demonstrated an infection rate of 7.6%. 21 The postcranioplasty infection rate among 151 PEEK implants in our series was 6%, and, as in other studies, suggests that synthetic prostheses have infection rates similar to those with ABFs. 4,14,19,23,25,[27][28][29] Most important in our results is the favorable comparison between protocols A and B as regards the reimplantation of +ABFs despite intraoperative bone cultures of skin flora.…”
Section: Discussionsupporting
confidence: 86%
“…Such timing is favored by some centers given reports of functional improvement after early cranioplasty. 1,7,11,21 Our data suggest that the ideal time for early cranioplasty, if desired, is probably between 14 and 30 days to balance the risk of infection with neurocognitive improvement since interrupting the wound healing process earlier than 14 days seems to predispose to subsequent wound complications.…”
Section: Discussionmentioning
confidence: 90%
“…Jalbert et al (Jalbert et al, 2014) operated on five patients with fronto-orbital defects in a single-step procedure for resection and reconstruction with a navigation device and PEEK PSI, with very good results and no major complications; this was similar to the experience of Kim et al (Kim et al, 2009), who reported four cases of maxillofacial defects. Rosenthal et al (Rosenthal et al, 2014) describe their experience with PEEK PSI in 66 cranioplasties at three different institutions. These authors reported a complication rate comparable to that of other implants or autologous bone, with an infection rate of 7.6% and a surgical removal rate of 9.1%, with overall satisfactory esthetic results.…”
Section: Discussionmentioning
confidence: 99%
“…No CSF leak was reported. The use of an autologous bone graft reduced the risk of infection compared with prosthetic materials, such as titanium, polyetheretherketone or polymethylmethacrylate [25,26]. Currently, we still perform iliac bone harvesting.…”
Section: Perioperative Reconstructionmentioning
confidence: 99%